(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Currently, one of the main tasks of teaching mathematics in primary school is to educate students as well-rounded individuals. In addition to providing mathematical knowledge, it is essential to ensure that the acquired knowledge is solid and well-founded, and to develop the skills and competencies necessary to apply that knowledge. Particularly in mathematics lessons, it is crucial to foster independent thinking skills and equip students with the necessary competencies to successfully apply acquired knowledge in real-life contexts. From this perspective, teaching students to solve mathematical problems, especially those based on real-life contexts and their own experiences, plays a key role in understanding the content and essence of mathematical concepts. Integrating such problems into the learning process enhances the relevance and practical application of education. Developing and implementing these methods contributes to improving the quality and effectiveness of instruction. This article outlines strategies and techniques that teachers can use to cultivate independent thinking culture among young learners, enabling them to analyze, question, and innovate in their academic and social activities.